A formação da identidade americana: pontos e contrapontos entre Macunaíma e Meridiano de sangue - Cruz, Diego da (2017)
This research study establishes a comparative analysis of Mário de Andrade’s Macunaíma, herói sem nenhum caráter and Cormac McCarthy’s Blood Meridian. Issues regarding language, violence and ambiguity are raised from a post-colonial perspective in order to discuss the identity of both nations in question - Brazilian and American. For this purpose, it discusses how Macunaíma and Blood Meridian approach or distance from each other as regards identity discussions of their contemporaneity. It also analyzes the fundamental characteristics of both books heroes in order to comparatively justify their formation concerning ambiguity, language and violence; and finally, it shows the convergence of Macunaíma and Blood Meridian aesthetics for the possibility of a postmodernist and post-colonialist reading perspective. The readings of Roberto Damatta (1997) and Roberto Reis (1987) concerning Brazil from the colonial period were essential, so that it was possible to discuss postcolonialism under the theories of Homi Bhabha (1998), Eduardo Coutinho (2003), Silviano Santiago (2000) and Boaventura de Sousa Santos (2009); Kimberle López (1998) and The Cambridge Companion to Cormac McCarthy (2013), organized by Steven Frye, were instrumental because of their importance in the postcolonial studies involving Macunaíma and Blood Meridian. Linda Hutcheon (1991), Stuart Hall (2006) and Eduardo Coutinho (2003), were the basic authors for the postmodernism understanding. Antonio Candido (1993) and Alfredo Bosi (1975) were theoretical basis for Macunaíma's aesthetic analysis, while Steven Frye (2013) and David Holloway (2003) were the basis for understanding McCarthy's work, so was An Outline of American History (1994) organized by Howard Cincotta. Since formation and a certain social structure are in vogue in Macunaíma, it is perceived in this work as Kid and Macunaíma shape their nations in the formation of their subjectivities, mainly the ambiguity that both possess as characteristic, Kid in his way of confronting violence and Macunaíma in his constant contradictions and transformations; the language of both also shapes an identity process, because while Kid inserts himself in a warlike context and it allows him to survive, Macunaíma needs to absorb anthropophagically the civilization and insert himself in a context of new codes of communication. Above all, the two works dialogue with the conflict of loss of authority, displacement, or even decimation of what has been considered the savage in the civilization process. While Macunaíma is the savage himself, who has to go to civilization to regain his possession that has been usurped, Kid constitutes the opposing force, which is literally usurping the Indians, their heads. They are, therefore, two very close discussions under different perspectives. It was found out that, although the novels were written in different contexts and time, Andrade and McCarthy similarly discuss their contemporary issues, by means of questions regarding identity, which gives a motto to the construction of their characters, language and style of their works. In this way, both authors converge to common post-colonial and post-modernist characteristics.